Utilization of Probiotics in Relieving Post-Colonoscopy Gastrointestinal Symptoms: A Systematic Review and Meta-Analysis. - Muzellina Virly Nanda; Alvianto Steven; Widjanarko Nicolas Daniel (Romanian Journal of Internal Medicine)
Colonoscopy is regarded as a safe diagnostic and therapeutic procedure, nevertheless, some patients may still encounter post-colonoscopy gastrointestinal symptoms. This study aimed to evaluate the utilization of probiotics before and after colonoscopy to relieve those symptoms.